Automation of decision making in management systems - Lewandowska, Maria; Zevnovak, Sergej (Zielona Góra: Uniwersytet Zielonogórski)
A model of decision making aimed at automation of an enterprise management system is presented. On the base of this model a procedure of decision making, taking into account the conditions of dynamically changing environment, was worked out.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka